Esculetin Inhibits Cancer Cell Glycolysis by Binding Tumor PGK2, GPD2, and GPI - Wu, Song-Tao; Liu, Bo; Ai, Zhong-Zhu; Hong, Zong-Chao; You, Peng-Tao; Wu, He-Zhen; Yang, Yan-Fang (Frontiers in Pharmacology, 2020)
Glycolysis can improve the tolerance of tissue cells to hypoxia, and its intermediates provide raw materials for the synthesis and metabolism of the tumor cells. If it can inhibit the activity of glycolysis-related enzymes and control the energy metabolism of tumor, it can be targeted for the treatment of malignant tumor. The target proteins phosphoglycerate kinase 2 (PGK2), glycerol-3-phosphate dehydrogenase (GPD2) and glucose-6-phosphate isomerase (GPI) were screened by combining transcriptome, proteomics and reverse docking. We detected the binding constant of the active compound using microscale thermophoresis (MST). It was found that esculetin bound well with three potential target proteins. Esculetin significantly inhibited the rate of glycolysis, manifested by differences of cellular lactate production and glucose consumption in HepG2 cells with or without esculetin. It was found that GPD2 bound strongly to GPI, revealing the direct interaction between the two glycolysis-related proteins. Animal tests have further demonstrated that esculetin may have anticancer effects by affecting the activity of PGK2, GPD2 and GPI. The results of this study demonstrated that esculetin could play an anti-tumor role by binding the glycolysis-related proteins to affect glucose and lipid metabolism, and these proteins which have direct interactions are potential novel targets for tumor treatment by esculetin.